Virtual Reality as an Assistive Technology to Support the Cognitive Development of People With Intellectual and Multiple Disabilities - Dutra da Cunha, Rian; da Silva, Rodrigo Luis de Souza (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2017)
This study investigated the efficacy of a virtual reality-based cognitive and motor coordination training for people with intellectual and multiple disabilities, focusing on community participation. Ten people with disabilities were selected from an institutional care for people with disabilities and they were enrolled in a five-week experiment, which consisted in shopping in a virtual reality supermarket. The results show that the patients demonstrated statistically significant improvements regarding the task gave, also based on the observational analysis of the instructor and physiotherapist. Thus, the analysis indicates that the VR-based method can be effective in the cognitive development of those patients, improving their social inclusion and cognitive skills.